Soil Biological Activity within Integrated and Ecological Management of Soil - Števlíková, Tatiana; Javoreková, Soňa; Vjatráková, Jana (Acta Agraria Debreceniensis, 2002)
The effects of the integrated (IS) and ecological (ES) management of soil on chosen parameters of soil biological activity were investigated in the period 1999-2000. The following characteristics were determined: biomass of microorganisms (Cmic), dehydrogenase activity (DHA), an amount of potentially mineralizable nitrogen (Nbiol), and nitrification intensity. Soil samples were collected from a stationary field experiment established in 1990 on gley brown soil at the Experimental Station of Slovak Agricultural University, Nitra. For each field with a different crop rotations two fertilization treatments were selected: (a) no fertilization and (b) use of manure for silage maize and, within IS, also mineral fertilizers. There was a statistically significant difference at α = 0.05 in the amount of biologically released nitrogen (Nbiol) between both systems and in the nitrification intensity in favour of ES. A higher amount of microbial biomass (Cmic) was noted for ES but without statistical significance. Cultivated crops and the timing of soil sampling were found to have the greatest effect on all the parameters observed in individual experimental years and within the two systems of soil management.